2006
DOI: 10.1038/sj.bjc.6603479
|View full text |Cite
|
Sign up to set email alerts
|

The status of CDKN2A alpha (p16INK4A) and beta (p14ARF) transcripts in thyroid tumour progression

Abstract: CDKN2A locus on chromosome 9p21 encodes two tumour suppressor proteins pl6 INK4A , which is a regulator of the retinoblastoma (RB) protein, and p14 ARF , which is involved in the ARF -Mdm2 -p53 pathway. The aim of this study was to determine if CDKN2A gene products are implicated in differentiated thyroid carcinogenesis and progression. We used real-time quantitative RT -PCR and immunohistochemistry to assess both transcripts and proteins levels in 60 tumours specimens. Overexpression of p14 ARF and pl6 INK4A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…INK4a in adenomas, papillary and follicular tumours, and the loss of expression in ATC was observed in previous works (Ferru et al 2006, Ball et al 2007, suggesting that p16…”
Section: Ink4amentioning
confidence: 88%
“…INK4a in adenomas, papillary and follicular tumours, and the loss of expression in ATC was observed in previous works (Ferru et al 2006, Ball et al 2007, suggesting that p16…”
Section: Ink4amentioning
confidence: 88%
“…In this regard, it is interesting to note that P16INK4a overexpression was significantly higher in MDM2+/CDK4+ WDLPS/DDLPS than in MDM2+/CDK4-WDLPS/DDLPS. P16INK4a overexpression has been reported in several tumor types such as gliomas (26), myxoid liposarcomas (27), thyroid carcinomas (28), and cervical carcinomas (29). P16INK4a overexpression might be a secondary event to RB1 inactivation, because RB1 repressed P16INK4a at the transcriptional level (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a target of CBX7 would be the CDKN2A/p16 tumor suppressor gene (11,12,33), suggesting that overexpression of CBX7 could enable cells to evade oncogeneinduced senescence; we then evaluated CDKN2A/p16 expression in (34,35), we show that CDKN2A/p16 is moderately overexpressed in PTCs and highly overexpressed in ATCs compared with normal thyroid tissues (Fig. 5).…”
Section: Cbx7 In Thyroid Carcinomasmentioning
confidence: 99%